Regulation, function, and expression of matrix metalloproteinase-9 in colon, lung, and breast cancers in silico and experimental methods from Iraqi metastatic patients - Hamad, Hamad Ali; Shakir, Yamama Farouk; Zaidan, Omar Tareq; Rafea, Aymen Adnan; Md Hashim, Nur Fariesha (Sciendo, 2024)
Background: Various molecular cancer variables, including K-RAS, B-RAF, and HER2/neu, are essential in the growth and advancement of tumors. Matrix metalloproteinase-9 (MMP-9) is suggested as a biomarker that is excessively produced in different types of malignancies and plays a critical role in chemotherapy resistance that leads to tumor progression and metastasis. Patients and Methods: The study used two different methods to evaluate the expression level of MMP9. First, we sought to find its expression and interaction with other proteins or genes using in slico techniques. Second, we evaluated the protein levels of MMP-9 in 80 metastatic patients with breast, colon, and lung cancer using enzyme-linked immunosorbent assay (ELISA) techniques. Results: In silico techniques showed a high expression of MMP9 gene in all three types of cancer. Furthermore, genes and proteins that interact the most with MMP9 were discovered using Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) and Human Protein Atlas (HPA). It was found that the genes associated with MMP9 gene in colon, lung, and breast cancers are MMP2 and TIMP2, along with MAPK, PI3K, and NF-κB pathways as the most significant genes and pathways across all three types of cancer that could be linked to the MMP9 gene in cancer metastasis. In addition, ELISA techniques showed that MMP9 was at the highest level in metastatic colon cancer patients at 0.62 ± 0.25, followed by breast and lung metastatic patients. Conclusion: MMP9 appears to play a crucial role in progression of particularly colon metastatic cancer and could be targeted alongside other genes as a possible therapeutic target for this type of cancer in patients with chemotherapy resistance and metastasis.